Unpacking professional vision: a cognitive task analysis of illustrators' liminal knowledge. - Oya-Haragi, Makiko; Kudo, Kuriko; Oga, Toru; Kiuchi, Takahiro (Cogent Arts & Humanities, 2025)
Visual authors' embodied knowledge generated power asymmetries that potentially distorted visuality through selective viewing and editing of visual content. However, this embodied knowledge remained unexplored due to its liminal position between academic and practical knowledge. This intermediary knowledge constituted what Goodwin termed 'professional vision'. This study unpacked the professional vision of twelve commercial illustrators employing Cognitive Task Analysis through focus group interviews. The analysis revealed a hierarchical structure comprising five subcategories of technical knowledge with 13 specific techniques, seven cognitive strategies, and six additional influential factors. Three critical findings emerged: first, fundamental techniques (Lines, Colouring, and Deformation) functioned as 'Explanatory Techniques' rather than purely aesthetic expressions; second, Purpose Clarification operated consistently across all illustration stages, with illustrators continuously articulating communicative intent; third, Visual Clarity constituted the most complex thematic element, requiring sophisticated integration of technical knowledge, cognitive skills, and community-based learning. These findings could illuminate how conscious intentionality distinguished professional practice, informing illustration pedagogy and controversial aesthetic debates AI-generated versus human-created imagery.